2010
DOI: 10.5012/bkcs.2010.31.02.339
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Catalytic Activity of Ce1MgxZr1-xO2(CMZO) Solid Heterogeneous Catalyst for the Synthesis of 5-Arylidine Barbituric acid Derivatives

Abstract: A series of Ce1MgxZr1-xO2 (CMZO) mixed metal oxide with different molar ratio were prepared by simple co-precipitation method. The prepared materials were tested for their catalytic activity performance using Knoevenagel condensation of various aromatic aldehydes with barbituric acid under solvent-free condition in microwave. The best catalytic activity was obtained with CMZO (1:0.6:0.4). The synthesized materials were characterized by using XRD, FT-IR, SEM-EDS techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…While peak observed at 420.9 °C is due desorption of NH3 from strong Lewis acidic sites. Figure 5(b) shows single peak at 308.9 °C is due to desorption of ammonia from Brönsted acidic sites [37]. From Table 1, the total acidity of parent mesolite and dealuminated mesolite is found 0.3724 and 0.5726 mmol.g -1 respectively.…”
Section: Temperature Programmed Ammonia Desorption (Nh3-tpd)mentioning
confidence: 91%
“…While peak observed at 420.9 °C is due desorption of NH3 from strong Lewis acidic sites. Figure 5(b) shows single peak at 308.9 °C is due to desorption of ammonia from Brönsted acidic sites [37]. From Table 1, the total acidity of parent mesolite and dealuminated mesolite is found 0.3724 and 0.5726 mmol.g -1 respectively.…”
Section: Temperature Programmed Ammonia Desorption (Nh3-tpd)mentioning
confidence: 91%
“…Catalytic activity results In continuation of our work to develop a new synthetic methodology, 34 herein, we would like to report an efficient and rapid method for the synthesis of 5-arylindene malononitriles via Knoevenagel condensation of aromatic aldehydes and malononitriles in the presence of catalytic amount of MCM-41 (CFA) in aqueous media. Initially, we carried out a model reaction of benzaldehyde with malonontrile using MCM-41 (0.1 gm) as a catalyst in distilled water (10 ml) was refluxed.…”
Section: 3233mentioning
confidence: 99%
“…The catalytic activity performance of cerium based bi-metallic nano particles with different weight percentage of molybdenum (8-20 wt% MoO 3 ) was also investigated. It was found that the activity of this bimetallic increases with increase in the Mo wt% loading (Rathod et al, 2010). Therefore, in this study bimetallic Mo/Ce catalyst has been employed as an effective catalyst for the production of CNTs.…”
Section: Introductionmentioning
confidence: 98%